Friction, acoustic emission, and wear mechanisms of a PEKK polymer. (April 2019) - Yahiaoui, M.; Chabert, F.; Paris, J.-Y.; Nassiet, V.; Denape, J.
Abstract: The tribological behavior of a steel/PEKK ball-on-flat contact was studied regarding the load, the velocity and the sliding distance in reciprocating or unidirectional motion. The friction measurements were synchronized with an acoustic emission (AE) device. The results show a behavior change associated with an adiabatic effect on the polymer when the mechanical energy input increases. Two interfacial mechanisms are also characterized: Schallamarch ridges and longitudinal ploughings. These mechanisms are related to two AE frequencies of 0.2 MHz and 1 MHz. The discussion on these two AE populations brings a stronger analysis and completes the friction and the wear mechanisms results. Highlights: The PEKK has a hysteretic behavior with phases of high (HF) and low friction (LF). The acoustic emission amplitude is higher during the LF phase. An adiabatic effect changes the PEKK rheology and its tribological behavior. The Schallamarch ridges formation is a source of acoustic emission at 1 MHz. Ploughing generates acoustic emission with a characteristic frequency of 200 KHz.